The Egyptian Muslim Brotherhood's transnational advocacy in Turkey: a new means of political participation. Issue 3 (27th May 2018) - Magued, Shaimaa
Abstract: This study examines the Egyptian Muslim Brotherhood's transnational media advocacy as a shift in the Islamists' political participation in general and the Brothers' in particular. The article argues that the Brothers created their own TV channels in order to challenge the new regime's legitimacy after 3 July 2013 by taking advantage of a sympathetic political environment in Turkey. Their media advocacy embraced a collective Islamic identity in its denunciation of the Sisi regime and called for a democratic restitution as a common Egyptian cause. Based on interviews conducted with TV presenters and a content analysis of the expatriates' TV channels, this study presents transnational advocacy as a novelty in the Islamists' repertoire of action.